Enhancing citizen engagement in planning through participatory film-making. (July 2021) - Manuel, Jen; Vigar, Geoff
There is a long history of engaging citizens in planning processes, and the intention to involve them actively in planning is a common objective. However, the reality of doing so is rather fraught and much empirical work suggests poor results. Partly in response an increasingly sophisticated toolkit of methods has emerged, and, in recent years, the deployment of various creative and digital technologies has enhanced this toolkit. We report here on case study research that deployed participatory film-making to augment a process of neighbourhood planning. We conclude that such a technology can elicit issues that might be missed in traditional planning processes; provoke key actors to include more citizens in the process by highlighting existing absences in the knowledge base; and, finally, provoke greater deliberation on issues by providing spaces for reflection and debate. We note, however, that while participants in film-making were positive about the experience, such creative methods were side-lined as established forms of technical–rational planning reasserted themselves.